The Role of Flipped Learning in Education: A Systematic Review on Physical Education and Sport Practices - SAĞIN, Ahmet Enes; YÜCEKAYA, Mehmet Akif (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2024)
This systematic review aims to comprehensively examine the effects of flipped learning (FL) on physical education (PE) and sports classes. To evaluate the applicability and effectiveness of the FL method in education, 17 studies published between 2019 and 2024 in the Web of Science (WoS) database were critically analyzed. The literature review was conducted in accordance with the PRISMA guidelines. For this systematic review, relevant articles were identified and selected using specific inclusion criteria and key terms in the WoS database. The studies chosen focus on the impact of educational technologies and FL in PE and sports. Each study was meticulously analyzed to evaluate the different aspects of FL. The main findings of the research indicate that FL is effective in enhancing student motivation and academic achievement. The reviewed studies reveal that FL positively influences students’ interest and participation in classes. Moreover, the integration of digital technologies increases the effectiveness of FL, providing students with easier access to educational materials.In conclusion, this review highlights the potential benefits of FL in PE and sports, while also emphasizing the need for further research to expand its applicability to larger student groups. These findings provide guidance for educators to use the FL method most effectively and support the widespread adoption of this approach in education.